Enterprise Resource Planning (ERP) Systems: Emergence, Importance and Challenges - Adnan Mustafa AlBar (The International Technology Management Review, 2014)
The Enterprise Resource Planning (ERP) has dawned as a tool to facilitate the flow of information and allow information sharing among different business partners. It appears as a response to the inappropriateness of the traditional systems which become outdated as a result of the change in business needs and the development of software programs. The use of ERP software has become more common in a lot of businesses nowadays. It appears as a complex and comprehensive software through which organizations can control and integrate all the business functions and processes in an extensive and innovative technique. This paper is dedicated to discuss enterprise resource planning, its emergence, implementation, importance of using it within organizations and the different challenges related to its implementation. Finally, discussion will be identified to review the most important issues and provide suggestions on the practical level to make effective use of this system.